Functional Characterization of the N Terminus of Sir3p - Gotta, Monica (American Society for Microbiology, 1998)
Silent information regulator 3 is an essential component of the Saccharomyces cerevisiae silencing complex that functions at telomeres and the silent mating-type loci, HMR and HML. We show that expression of the N- and C-terminal-encoding halves of SIR3 in trans partially complements the mating defect of the sir3 null allele, suggesting that the two domains have distinct functions. We present here a functional characterization of these domains. The N-terminal domain (Sir3N) increases both the frequency and extent of telomere-proximal silencing when expressed ectopically in SIR(+) yeast strains, although we are unable to detect interaction between this domain and any known components of the silencing machinery. In contrast to its effect at telomeres, Sir3N overexpression derepresses transcription of reporter genes inserted in the ribosomal DNA (rDNA) array. Immunolocalization of Sir3N-GFP and Sir2p suggests that Sir3N directly antagonizes nucleolar Sir2p, releasing an rDNA-bound population of Sir2p so that it can enhance repression at telomeres. Overexpression of the C-terminal domain of either Sir3p or Sir4p has a dominant-negative effect on telomeric silencing. In strains overexpressing the C-terminal domain of Sir4p, elevated expression of either full-length Sir3p or Sir3N restores repression and the punctate pattern of Sir3p and Rap1p immunostaining. The similarity of Sir3N and Sir3p overexpression phenotypes suggests that Sir3N acts as an allosteric effector of Sir3p, either enhancing its interactions with other silencing components or liberating the full-length protein from nonfunctional complexes.